Checklist of spiders in Tasek Bera Ramsar Site, Pahang, Malaysia - Chooi, Y. S.; Tan, P. E.; Lau, Wei Hong (Department of Wildlife and National Parks (DWNP) Peninsular Malaysia, 2014)
Established since 1995, Tasek Bera is a wetland of international importance. It comprises an area of 31,120 hectares. It is the largest natural freshwater lake in Malaysia. The natural freshwater lake is rich in local flora and fauna. A study of the biodiversity of spider was carried out during the Biodiversity Inventory Program at Tasek Bera Ramsar Site, Pahang from 20th to 26th May 2009. Throughout the program a total of 216 spiders were collected. Among them, 13 families of spider, namely the Agelenidae, Araneidae, Lycosidae, Nephilidae, Oxyopidae, Pholcidae, Pisauridae, Psechridae, Salticidae, Sparassidae, Tetragnathidae, Theridiidae, and Thomisidae were recorded. Most spiders found on web built between branches are the members of Araneidae, Nephilidae, Psechridae, Tetragnathidae, and Theridiidae while others were either foraging on trees (Oxyopidae, Pholcidae, Pisauridae, and Salticidae) or on the ground (Agelenidae, Lycosidae, and Sparassidae). A high variety of spider species were recorded.